2008
DOI: 10.1016/j.str.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neurexin 1β Tertiary Structure and Ligand Binding through Alternative Splicing

Abstract: Neurexins and neuroligins play an essential role in synapse function, and their alterations are linked to autistic spectrum disorder. Interactions between neurexins and neuroligins regulate inhibitory and excitatory synaptogenesis in vitro through a "splice-insert signaling code." In particular, neurexin 1beta carrying an alternative splice insert at site SS#4 interacts with neuroligin 2 (found predominantly at inhibitory synapses) but much less so with other neuroligins (those carrying an insert at site B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 51 publications
3
68
0
Order By: Relevance
“…S1). Ca 2ϩ binding in Nrxn (by D137, V154, I236 and N238 for ␤-Nrxn), agrin, and laminins represents a rigid ''socket'' with no f lexible states as in EF hands (23), consistent with unchanged CD spectra of Nrxn and agrin (13,38) and crystal data (15)(16)(17)39). This rigidity allowed us to transfer epitopes from other LNS domains to Nrxn: ␤N238G mimics the Ca 2ϩ coordination of Nrxn LNS2 but reduced Ca 2ϩ affinity of the Nrxn/Nlgn complex Ϸ200-fold (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…S1). Ca 2ϩ binding in Nrxn (by D137, V154, I236 and N238 for ␤-Nrxn), agrin, and laminins represents a rigid ''socket'' with no f lexible states as in EF hands (23), consistent with unchanged CD spectra of Nrxn and agrin (13,38) and crystal data (15)(16)(17)39). This rigidity allowed us to transfer epitopes from other LNS domains to Nrxn: ␤N238G mimics the Ca 2ϩ coordination of Nrxn LNS2 but reduced Ca 2ϩ affinity of the Nrxn/Nlgn complex Ϸ200-fold (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Because the complex still forms with this mutation at physiological [Ca 2ϩ ], it appears unlikely that calcium affinity itself defines splice-code-specific pairings (21). Rather, crystal and NMR data revealed that insert SS4 exists in an equilibrium of two conformations (39,40). The inactive form is stabilized by coordinating Ca 2ϩ with high affinity (39), whereas binding follows after unfolding of SS4 (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They bind to presynaptic alpha and beta forms of Neurexins (Ichtchenko et al, 1995(Ichtchenko et al, , 1996Missler et al, 1998;Boucard et al, 2005) and the alternative splicing of both protein families controls their binding affinities (Boucard et al, 2005;Chih et al, 2006;Comoletti et al, 2006;Fabrichny et al, 2007;Koehnke et al, 2008a,b;Shen et al, 2008). The current data suggest that Neurexin-Neuroligin binding is governed by a complex code that is based on the type of isoforms and splice variants involved, calcium binding, and glycosylation (Sudhof, 2008).…”
Section: Introductionmentioning
confidence: 62%
“…Purified hexahistidinetagged bovine neurexin 1␣ and its fragments as well as hexahistidine-tagged rat neuroligin 2 (NL2) containing insert ϩA2 were produced in a manner similar to that described previously (16). Recombinant rat neurexin 1␤ was produced as described (26). For analytical size exclusion chromatography, proteins were loaded on a Superdex 200 PC 3.2/30 column in 25 mM Tris, pH 8.0, 120 mM NaCl, 5 mM CaCl 2 and run at 0.08 ml/min.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%